IMPLEMENTASI AUTOMATIC EXCHANGE of FINANCIAL ACCOUNT INFORMATION (AEOI) DI INDONESIA - Baginda Parsaulian (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Implementation of Automatic Exchange of Financial Account Information (AEOI) in Indonesia At present there are 100 countries or jurisdictions including Indonesia, have stated their commitment to implement financial information exchanges automatically based on the Common Reporting Standard (CRS), which was compiled by the Organization for Economic Cooperation and Development (OECD) and G20. The method used in writing this article is the literature review. Interim government regulation No. 1 of 2017 concerning access to Financial Information for Taxation Interests was set on May 8, 2017 as a legal for implementing the Automatic Exchange of Financial Information (AEOI) in Indonesia. This article aims to provide an overview of the implementation of the agreement on the Automatic Exchange of Financial Information (AEOI) in Indonesia.Implementasi Automatic Exchange of Financial Account Information (AEOI) di Indonesia. Saat ini terdapat 100 negara atau yurisdiksi termasuk Indonesia, telah menyatakan komitmennya untuk mengimplementasikan pertukaran informasi keuangan secara otomatis berdasarkan Common Reporting Standard (CRS), yang disusun oleh Organization for Economic Cooperation and Development (OECD) dan G20. Metode yang digunakan dalam penulisan artikel ini adalah literature review. Peraturan Pemerintah Pengganti Undang-Undang No. 1 Tahun 2017 tentang Akses Informasi Keuangan untuk Kepentingan Perpajakan ditetapkan tanggal 8 Mei 2017 sebagai payung hukum pelaksanaan implementasi Automatic Exchange of Financial Information (AEOI) di Indonesia. Artikel ini bertujuan untuk memberikan gambaran mengenai implementasi pelaksanaan kesepakatan Automatic Exchange of Financial Information (AEOI) di Indonesia.